Prevalence of isolated hand problems in physiotherapy and rehabilitation centres in Istanbul - (:unkn) unknown (My University, 2013)
Purpose: This study examined prevalence of isolated hand problems in physiotherapy and rehabilitation patients. Methods: Patient files of 21.450 patients (51.14±15.85 years, 14.973 females, 6.477 males) admitted to physiotherapy and rehabilitation program in Istanbul Balat Jewish Hospital, Duygu Hospital and Burcu Physiotherapy Centre between January 2006 and February 2010 were examined. The reason for admission and primary pathology were recorded. Results: Treatment was required due to hand or wrist problems in 665 (3.1%) patients, and due to other pathologies in 20.785 (96.9%) patients. Causes of hand and wrist problems (n=665) were hemiplegic hand in 150 (22.6%), carpal contracture in 124 (18.7%), bilateral carpal tunnel syndrome in 116 (17.4%), hand contracture in 81 (12.2%), De-Quervain in 40 (6.0%), synovitis and tenosynovitis 37 (5.56%), unilateral carpal tunnel syndrome in 17 (2.6%), rheumatoid arthritis of the hand in 17 (2.6%), and Dupuytren's contracture in 10 (1.5%) patients. De Quervain, bilateral carpal tunnel syndrome, synovitis and tenosynovitis and carpal contracture were found to be more frequent in females, while hemiplegic hand and carpal contracture were found to be more frequent in males (p<0.05). Conclusion: Hand and wrist problems were seen in very low rates of among our patients as compared to other neuromusculoskeletal problems. The most frequent problems were hemiplegic hand, carpal contracture, carpal tunnel syndrome, and hand contracture. There are differences in the frequency between female and male genders.
Keywords: Hand; Physiotherapy; Prevalence; Turkey